O Idoso Coloca a Morte em Cena: Reflexões Sobre a Prática Médica Sob a Perspectiva da Reumanização da Morte nos Cuidados Paliativos - Oliveira, João Batista Alves de (2006)
This dissertation brings a bibliographical review about death, but it is not a mere compilation of facts, but above all it hands a new humanistic version regarding this theme, by means of mythological, philosophical and poetical approach. Much more than an academic text, it intends to be thoughtful and contribute towards the humanization of death, which has been left aside for centuries and many times, nowadays, dealt with so mechanical and technically. It not only restates the finite human thing like our most constituent characteristic, but also the importance doctors should pay towards humanizing the treatment, having based on the Palliative Care philosophy, especially at old age for it is the phase in which patients in dying process i.e. facing death most demand care. It does not claim the creation of rules, labels, nor stipulates conduct, but creates some awareness of the importance to doctors becoming closer to patients, making it possible the re-humanization of death